The Effectiveness of Shadow Training on Improving the Responsiveness of Drop Shots in Badminton - Moh. Hafidz Alfa Rizqi; Mohamad Da'i; Hilmy Aliriad; Afdol Febriansyah (Universitas Negeri Semarang, 2026)
Badminton is a popular sport in Indonesia and requires a thorough mastery of basic techniques to control the game and effectively place the shuttlecock in the opponent's court. One crucial technique is the drop shot, which demands precision, control, and high responsiveness, including reaction time, precise shot execution, and decision-making skills in game situations.This study aims to evaluate the effectiveness of shadow training in improving the responsiveness of drop shots in badminton players. The method used was a quasi-experimental one-group pretest–posttest design, involving 23 eighth-grade students of MTs Islamiyah Tulungagung who were divided into experimental and control groups. The experimental group underwent shadow training for six weeks at a frequency of once per week, while the control group received no special treatment. The research instrument was a drop shot accuracy test that measures reaction speed and shot accuracy. Data analysis used descriptive and inferential statistics, including the Shapiro–Wilk normality test and paired t-test. The results showed that the experimental group experienced a significant increase (sig. 0.001; the mean increased from 0.01 to 27.36), while the control group showed no significant increase (sig. 0.082). These findings confirm that shadow training is effective in improving the responsiveness of drop shots and supports the development of motor coordination, motor readiness, and technical quality of players. Therefore, shadow training can be recommended as a systematic and applicable training method for the overall development of badminton athletes' abilities.